Accounting for the Nutrients in Reclaimed Water for Landscape Irrigation - Christopher J. Martinez; Mark W. Clark; Gurpal S. Toor; George J. Hochmuth; Lawrence R. Parsons (EDIS)
This 8-page fact sheet presents basic information for those using reclaimed water to irrigate lawns and landscapes. The information can serve as a guide to determine whether there is an opportunity to replace some of the fertilizer that might otherwise be applied and to offer guidance on avoiding runoff and leaching of excess nutrients. Written by Christopher J. Martinez, Mark W. Clark, Gurpal S. Toor, George J. Hochmuth, and Lawrence R. Parsons, and published by the UF Department of Agricultural and Biological Engineering, August 2011. (UF/IFAS photo by Marisol Amador)